2013
DOI: 10.1371/journal.pone.0067062
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Programmatic Gaps: Inequities in Harm Reduction Service Utilization among Male and Female Drug Users in Dar es Salaam, Tanzania

Abstract: IntroductionCurrent estimates suggest an HIV prevalence of 42% among people who inject drugs (PWIDs) in Dar es Salaam, while HIV prevalence is estimated to be 8.8% among the general population in the city. To address the HIV epidemic in this population, the government of Tanzania began establishing HIV prevention, treatment and care services including outreach and medication assisted treatment (MAT) for PWIDs in 2010. We assessed gender inequities in utilization of outreach and MAT services and evaluated diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 17 publications
3
56
0
Order By: Relevance
“…Males participated significantly more than females in the program sessions, which is consistent with international studies reported gender inequity in access to harm reduction services both in developed (27) and in developing countries (28). Despite the higher frequency of methamphetamine use and lower rate of participation in the intervention among females, analysis of data by gender revealed that an increase in the percentage of condom use in the last sexual intercourse and a decrease in unprotected sex due to methamphetamine effects were significant among females, but the decreasing trend was not significant among males.…”
Section: Discussionsupporting
confidence: 87%
“…Males participated significantly more than females in the program sessions, which is consistent with international studies reported gender inequity in access to harm reduction services both in developed (27) and in developing countries (28). Despite the higher frequency of methamphetamine use and lower rate of participation in the intervention among females, analysis of data by gender revealed that an increase in the percentage of condom use in the last sexual intercourse and a decrease in unprotected sex due to methamphetamine effects were significant among females, but the decreasing trend was not significant among males.…”
Section: Discussionsupporting
confidence: 87%
“…In Tanzania, 85% of FWID are sex workers and their HIV prevalence is 62%, compared to 28% among MWID (Lambdin et al, 2013)…”
Section: Women Drug Use and Sex Workmentioning
confidence: 99%
“…Further, there is high overlap between female PWID and sex work in Dar es Salaam, with an estimated 31% of female PWID engaging in commercial sex work as compared to less than 1% for males. 43 …”
Section: People Who Inject Drugs (Pwid)mentioning
confidence: 99%